The effect of the patient protection and affordable care act medicaid expansions on financial wellbeing - Luojia Hu; Robert Kaestner; Bhashkar Mazumder; Sarah Miller; Ashley Wong (Federal Reserve Bank of Chicago, 2016)
We examine the effect of the Medicaid expansions under the 2010 Patient Protection and Affordable Care Act (ACA) on consumer, financial outcomes using data from a major credit reporting agency for a large, national sample of adults. We employ the synthetic control method to compare individuals living in states that expanded Medicaid to those that did not. We find that the Medicaid expansions significantly reduced the number of unpaid bills and the amount of debt sent to third-party collection agencies among those residing in zip codes with the highest share of low-income, uninsured individuals. Our estimates imply a reduction in collection balances of between 600 to 1,000 among those who gain Medicaid coverage due to the ACA. Our findings suggest that the ACA Medicaid expansions had important financial impacts beyond health care use.
Keywords: I12; I18; H42; 330; health insurance; consumer finance; public policy; Gesetzliche Krankenversicherung; Versicherungsschutz; Wirkungsanalyse; Niedrigeinkommen; Private Verschuldung; Schätzung; USA